Production Performance of Meat and Eggs of Domestic Quail: Potential and Utilization as Genetic Resources - Tamzil, Mohammad Hasil; Wiryawan, Ketut Gede; Septian, I Gede Nano (Jurnal Biologi Tropis, 2025)
This review article is written to provide information to readers regarding the potential of quail as a genetic resource of poultry for poultry-based food production. Quail was first domesticated in Japan and has strong potential for development as both a meat and egg producer. This species is known for its high feed efficiency in meat production, characterized by a high carcass yield, dominant meat deposition in the breast and thigh, and a superior meat-to-bone ratio compared to native chickens and broilers. In addition, quail demonstrates egg production capabilities that are nearly comparable to those of commercial laying hens, although with slightly lower feed efficiency. Based on these characteristics, quail is worthy of consideration as a genetic resource of poultry that is efficient and economical in providing animal protein.